2011
DOI: 10.4103/2229-4708.90364
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the UV-spectrophotometric method for determination of terbinafine hydrochloride in bulk and in formulation

Abstract: Background:The main objective was to develop and validate the UV-spectrophotometric method for the estimation of terbinafine hydrochloride in bulk and pharmaceutical formulations as per ICH guidelinesMaterials and Methods:A simple, rapid, accurate, and economical UV-spectrophotometric method has been developed for the estimation of terbinafine hydrochloride from bulk and pharmaceutical formulation.Results:The λmax of terbinafine hydrochloride in water was found to be 283 nm. The drug follows linearity in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…The results obtained were used to calculate the equation of the line by using linear regression by the leastsquares regression method [16].…”
Section: Validation Of Methods Linearitymentioning
confidence: 99%
“…The results obtained were used to calculate the equation of the line by using linear regression by the leastsquares regression method [16].…”
Section: Validation Of Methods Linearitymentioning
confidence: 99%
“…From the resulting absorbance, the standard deviation and relative standard deviation were calculated [30].…”
Section: Repeatabilitymentioning
confidence: 99%
“…The ruggedness of the proposed method was determined for 20 μg/ml concentration of HQ by analysis of aliquots from a homogenous slot by two analysts using same operational and environmental conditions [30].…”
Section: Ruggednessmentioning
confidence: 99%
“…Literature review revealed the determination of sitagliptin in dosage form either alone or combined form by UV spectrophotometry [13][14][15] , RP-HPLC 5,16-21 , UPLC 22 , tandem mass spectrometry 23,24 and capillary electrophoresis. 25 However, UV spectrophotometry is the simplest technique but it is deficient in accuracy and precision and needs relatively higher amount of analytes for detection.…”
Section: Sitagliptin Chemically [(R)mentioning
confidence: 99%